PRAKTEK-PRAKTEK PENGELOLAAN SUMBER DAYA MANUSIA DALAM BISNIS MODERN UNTUK MERAIH KEUNGGULAN KOMPETITIF - Hendra Permadi; Sugeng Prayetno (Media Bina Ilmiah, 2023)
This study uses library research. Changes in the business environment are indicated by the development of communication technology as well as information technology is the main challenge faced by HR today. Rapid advances in technology provide convenience in the application of company operational activities. This condition causes workers who have low potential to be unable to compete because with technological developments, companies no longer need blue collar workers, but employees who are able to master existing technological developments and have managerial talent. IT has a specific role in managing tablespoons through innovation in HR information technology. an example of an application is through People soft or SAP using the Human Resources Information System (HRIS). As a result, rapid technological changes require new skills that can be obtained from empowerment, education and training, organizations that are increasingly complex, flatter and leaner organizations that are more flexible, demographic changes with the limited availability of manpower, the need for a more frequent response with strength. external forces such as legislation and regulations, and increasing multinational competence, multilateral cooperation and correlations (Sculler and Walker, 1990). In other words, human resources involved in company processes or activities must mean human resources who have a knowledge base (knowledge-based worker) who has a variety of skills and expertise (multi-skilling worker).